The equation is (1-sin2x)(1+sin2x) = 1+sin2x-sin2x- (sin2x)(sin2x)
Does that equal = 1 - 2sin2x or 1 - (sin2x)^2 = 1- sin4x^2 ?? I have not done this before
It would be very strange to be given problems like this involving sine if you have never taken an algebra class. But if you have taken algebra then surely you should know that (a+ b)(a- b)= a^2+ ab- ab- b^2= a^2- b^2. So (1- sin(2x))(1+ sin(2x))= 1- sin^2(2x). No, the square does does NOT apply to the argument, 2x, of the sine, it applies to the sine itself.